Not Just Mind Over Matter: Reviewing With Patients How Mindfulness Relieves Chronic Low Back Pain - Natalia E. Morone MD, MS (SAGE Publishing, 2019)
The current opioid crisis has spurred the need for nonpharmacological therapies for chronic low back pain. In a study published in JAMA Internal Medicine , we reported that in 282 older adults with chronic low back pain, an 8-week mind-body group program modeled on Mindfulness-Based Stress Reduction (MBSR) decreased long-term pain and increased short-term function. Barriers to uptake remain such as patient resistance to accepting the benefits of nonpharmacological treatments for chronic low back pain. They may fear the clinician does not believe their pain complaint because they are not being offered a pain pill. By not appreciating the value of the therapy in helping their chronic low back pain, the patient may not be compliant with recommendations. Resistance likely derives from lack of understanding how a mind-body approach like MBSR can help relieve the sensation of pain as well as help increase function. Clinicians can help break through this barrier by educating their patients about the different ways in which MBSR works to reduce pain and improve function. In this commentary, we will discuss how our findings can inform the discussion clinicians have with their patients regarding the ways MBSR can relieve back pain. Pain processing is complex and top-down regulation is not fully engaged when pain is treated with pharmacotherapy alone. We share that our study showed a clinically meaningful reduction in pain and improvement in function and discuss some of the possible underlying mechanisms of MBSR's effect.